Disappearance of boreal plants in southern Britain: habitat loss or climate change?. (23rd March 2015) - Hill, Mark O.; Preston, Christopher D.
<x xml:space="preserve">Abstract</x> Vascular plant and bryophyte species whose geographical range is mainly in the boreal zone have declined markedly in southern Britain since records began. Some of this decline can be attributed to a loss of habitat rather than climate change. In the present study, we estimate the loss attributable to climate change by setting up paired comparisons. In the zone of Britain with July mean temperature greater than 15 °C in the 30‐year period 1961–1990, each boreal species was matched with a more southern one having similar frequency, size, and ecological attributes. Because both members of each pair have similar ecological attributes, they should suffer equally from habitat loss and degradation, allowing change attributable to differences in phytogeographical character to be separated out. Hectad (10 km2) records of presence in the period 2000–2013 were compared with those from 1970–1999. Boreal vascular plants decreased by approximately 41%, whereas their matched more southern species decreased by approximately 24%. For 39 of 53 matched pairs, the boreal partner decreased more than its southern comparator, a disparity most unlikely to be a result of chance. Declines for bryophytes averaged 15% for boreal species and 15% for their partners. We conclude that climate change is now having an effect comparable to that of habitat loss on boreal vascular plants in southern Britain but not on boreal bryophytes. © 2015 The Linnean Society of London, Biological Journal of the Linnean Society, 2015, ●●, ●●–●●.